Determination of parameters of canning of rabbit meat (Oryctolagus cuniculus) - Ygnacio Santa Cruz, Abraham Guillermo (2017)
The objective of the research was to determine the optimum parameters of rabbit meat canning for human consumption. Rabbit meat is a protein-rich food with less fat than red meats. Six months old male rabbits, which had an average weight of 1.900 g were used, a brine solution was used in three concentrations at 1.8%, 2% and 2.2% of sodium chloride, the process sterilization of the preserves was performed in an autoclave at a constant temperature of 122 ° C. in the retort, and working times of 30, 35 and 40 minutes, the cooling was performed by circulating water inside the autoclave, cooled to a temperature of 45 ° C . Approximately to be removed from the autoclave; The product was stored under moderate light conditions at room temperature (25 ° C) and incubation temperature (37 ° C) for 90 days. The results of the organoleptic evaluation indicated that the best treatments were the following: liquid of 2% of sodium chloride, final heat treatment of 122 ºC. To a working time of 35 minutes.